Dietary plant flavonoid supplementation for poultry as a potent scavenger of hydroxyl radicals and antioxidants: a review - Negasa,Jiregna Gari (PeerJ Organic Chemistry, 2024)
The poultry industry is paying more attention to plant-based feed additives. Flavonoids are plant secondary metabolites derived from fruits, grains, vegetables, herbs, and medicinal plants. One of the most significant environmental stressors affecting the poultry industry worldwide is heat stress, which lowers the quality and safety of production. An imbalance between the production of free radicals and the body’s natural antioxidant defenses leads to oxidative stress in cells. These reactive species can damage proteins, lipids, DNA, and cellular structures. Improving the antioxidant status of poultry bodies by feeding them antioxidant-supplemented feed can increase productivity and health. Plant flavonoid compounds have drawn attention from researchers as possible natural antioxidant sources because of their potential for use as feed additives in poultry production. Numerous studies have demonstrated that dietary flavonoids have strong antioxidant effects and can be utilized as a tonic in poultry to improve health and productivity. Overall, research on the antioxidant capacity of plant flavonoids has generally shown promising results; however, there are still significant issues regarding the detrimental effects of flavonoids to be resolved, and measuring oxidative damage in vivo is challenging. This review summarizes the current understanding of dietary plant flavonoid supplementation for poultry as a potent scavenger of hydroxyl radicals and antioxidants.
Keywords: Flavonoid; Antioxidant; Poultry; Hydroxyl radical; Oxidative stress